Impression of Twitter and Whatsapp on Sleep Quality Among Nursing Students In Indonesia - Yosi Maria Wijaya; Fransiskus Xaverius Widiantoro (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: The widely used social media by mobile-platform, which makes communication easier, faster, enhance effective flow of information. However, it may have the potential negative effect in quality of sleep in nursing students. The purpose of this study was to examined the impact of using social media and identified predictors of poor sleep quality among nursing students. Methods: A school-based survey design was conducted. Totally, 264 students at school of health sciences in West Java with usage social media platform were participated in this study. The extensive self-administered questionnaires were used to assess extent of using social media and the Pittsburgh Sleep Quality Index. Logistic regression analysis by a backward-stepwise technique was used to determine predictors of poor sleep quality. Results: One out of two nursing students (59.5 %) used both Instagram and WhatsApp, mostly at nights (59.8%), and more than 4-hour daily (19.3%). Majority nursing students (94.3%) have poor quality of sleep. Quality of sleep was differed significantly in bachelor students (p=0.03) in 8th semester (p = 0.006). Younger nursing students (β = 0.025, p = 0.021, 95% CI 0.001-0.566) who use social media less than 3-month (β = .019, p = 0.001, 95% CI 0.002-0.212), mostly during weekends and in 8th semester (β = 41.32, p = 0.018, 95% CI 1.902-897.73) were predictor of poorer sleep quality. Conclusion: Findings indicated a strong need for integrating sleep quality education and provide health-education to promote correct and effective use of social networks to minimize possible side effects in nursing students.